Predictors of prevalent statin use among older adults identified as statin initiators based on Medicare claims data. Issue 7 (15th March 2016) - Young, Jessica C.; Stürmer, Til; Lund, Jennifer L.; Funk, Michele Jonsson
Abstract: Purpose: Few studies have evaluated the degree to which prescription drug initiators are correctly identified using claims data. We examine the prevalence and predictors of recent statin possession in statin initiators identified using claims data. Methods: Among Medicare Current Beneficiary Survey (MCBS) respondents, we used Medicare Part D claims from 2006 to 2011 to identify statin initiators using a 12‐month baseline period of no prior statin claims. Using MCBS interview data, we identified those with self‐reported statins obtained during the baseline period. We used log‐binomial regression to estimate adjusted prevalence ratios (adjPR) and 95% confidence intervals (CI) for predictors of recent statin possession. Results: Among 766 statin initiators identified in prescription claims, 155 (20%) reported recent statin possession during baseline. Beneficiaries with no Part D claims in the past 30 days (adjPR = 1.49, 95%CI: 1.13, 1.96), those with no inpatient, outpatient or physician visits in the past 30 days (adjPR = 1.50, 95%CI: 1.11, 2.03), those with a brand name statin index claim (adjPR = 1.55, 95%CI: 1.19, 2.02), and those with an index claim in January or February (adjPR = 1.50, 95%CI: 1.00, 2.26) had an increased probability of recent statin possession. Conclusions: In a cohort of statin initiators identified using prescription claims, 20% had evidence of statin possession during the baseline period. Pharmacoepidemiologic new user studies may benefit from including sensitivity analyses within subgroups less likely to include prevalent users to assess the robustness of key findings to misidentification of the time of treatment initiation. Copyright © 2016 John Wiley & Sons, Ltd.